Exploring the potential of using nudges to promote food hygiene in the pork value chain in Vietnam - Hennessey, M.; Kim, S.; Unger, Fred; Hung Nguyen-Viet; Sinh Dang-Xuan; Thinh Nguyen-Thi; Häsler, Barbara (Elsevier, 2020)
Interventions designed to reduce the burden of foodborne illness often require value chain actors to alter undesired and risky behaviours. This desired behavioural change may be supported by ‘nudge theory’, a sub-field of behavioural economics, which describes how individuals can be encouraged, or ‘nudged’, to act in ways which produce net societal benefits without restricting freedom of choice.